Reduction of dimensionality in dynamic programming-based solution methods for nonlinear integer programming - Balasubramanian Ram; A. J. G. Babu (International Journal of Mathematics and Mathematical Sciences)
This paper suggests a method of formulating any nonlinear integer programming problem, with any number of constraints, as an equivalent single constraint problem, thus reducing the dimensionality of the associated dynamic programming problem.